2020
DOI: 10.1038/s41598-020-68300-y
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal posterior cingulate cortex encodes the informational value of feedback in human–computer interaction

Abstract: Behavioural results. Table 1 shows the descriptive statistics (means and standard errors) for accuracy rates and reaction times for each of the six experimental conditions. Visual inspection of Q-Q plots, skewness (all |S| < 0.95 , all p > 0.05), kurtosis (all |K| < 1.31 , all p > 0.05), and Shapiro-Wilk tests (all W > 0.91 , all p > 0.05) showed no significant deviations from normal distribution. Neither of the repeated-measures ANOVAs revealed significant main effects or interaction effects of informational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…The dPCC shows strong connectivity with the rest of the DMN, but is also functionally highly connected to the frontoparietal networks of attention and executive control, suggesting a more prominent role of dPCC in cognitive control (39,40). A recent study reported increased activity of the dPCC (specifically area d23) during evaluative feedback concerning the correctness of a decision, demonstrating the dorsal PCC to be involved in the behavioral adaptation to information from the environment (41).…”
Section: Discussionmentioning
confidence: 99%
“…The dPCC shows strong connectivity with the rest of the DMN, but is also functionally highly connected to the frontoparietal networks of attention and executive control, suggesting a more prominent role of dPCC in cognitive control (39,40). A recent study reported increased activity of the dPCC (specifically area d23) during evaluative feedback concerning the correctness of a decision, demonstrating the dorsal PCC to be involved in the behavioral adaptation to information from the environment (41).…”
Section: Discussionmentioning
confidence: 99%
“…Among the regions of the GMV, the subcallosal cortex stands out under its distinctive role. One study revealed that the subcallosal cortex called the limbic system, was involved in higher nervous, mental, and visceral activities [ 36 , 37 ]. At the same time, the function of the lateral occipital cortex was preferentially involved in the transmission and processing of negative emotions and plays a critical role in emotional processing [ 38 ], which has been noted in several anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This could have led to differences in anticipation or outcome prediction between the two primary conditions (i.e., meditation and rest) being compared. However, these anticipatory effects may have been minimal, as brain areas pertaining to outcome prediction, anticipation and motor planning (Alexander & Brown, 2011; Thickbroom et al, 2000; Wolff et al, 2020) either showed no response (e.g., no activation in dorsal thalamus, supplementary motor areas) or demonstrated deactivation instead of activation (e.g., mPFC deactivation) during meditation relative to rest.…”
Section: Discussionmentioning
confidence: 99%